2016
DOI: 10.1371/journal.pone.0145649
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Monochorionicity and Twin to Twin Transfusion Syndrome on Prenatal Attachment, Post Traumatic Stress Disorder, Anxiety and Depressive Symptoms

Abstract: Monochronioric (MC) twin pregnancies are considered as high-risk pregnancies with potential complications requiring in-utero interventions. We aimed to assess prenatal attachment, anxiety, post-traumatic stress disorder (PTSD) and depressive symptoms in MC pregnancies complicated with Twin-To-Twin-transfusion syndrome (TTTS) in comparison to uncomplicated monochorionic (UMC) and dichorionic pregnancies (DC). Auto-questionnaires were filled out at diagnosis of TTTS and at successive milestones. Prenatal attachm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 43 publications
1
17
1
1
Order By: Relevance
“…Finally, the treatment and the monitoring of TTTs are highly anxiogenic and may cause psychological disorders during subsequent pregnancies. 22 In our study, the prevalence of anxiety in subsequent pregnancies was as high as 39.2%, although the difference with the control group was not significant. Most of these women described a permanent "fear of losing the baby."…”
Section: Discussioncontrasting
confidence: 61%
“…Finally, the treatment and the monitoring of TTTs are highly anxiogenic and may cause psychological disorders during subsequent pregnancies. 22 In our study, the prevalence of anxiety in subsequent pregnancies was as high as 39.2%, although the difference with the control group was not significant. Most of these women described a permanent "fear of losing the baby."…”
Section: Discussioncontrasting
confidence: 61%
“…Despite previous works on prenatal attachment in mother of twins observed that it may be a risk factor for the development of a close and positive relationship between the mother and the babies, as far as we know, only six studies explored prenatal attachment in twin pregnancies [13,19,48,[75][76][77].…”
Section: Prenatal Attachment In Twin Pregnancy: a Review Of Existing mentioning
confidence: 97%
“…In particular, it was showed that the increase of prenatal attachment in the last trimester of pregnancy, usually described in singleton pregnancies [78], was observed both in dichorionic and uncomplicated monochorionic pregnancies, while this intensification was not observed in pregnancies complicated by TTTS. The fear represented by the high risk associated to TTTS pregnancies, the uncertainty for the pregnancy outcome and the doubt for the health of the fetus seemed to reduce prenatal attachment [13].…”
Section: Prenatal Attachment In Twin Pregnancy: a Review Of Existing mentioning
confidence: 99%
See 1 more Smart Citation
“…Sağlıklı gebelerde gebelik haftası ilerledikçe yaklaşan doğum sürecinin etkisi ile kaygı ve depresyon artmaktadır [25]. Ancak Fransa ve Almanya'da riskli gebelerle yapılan çalışmalarda anksiyetenin gebelik ilerledikçe bizim çalışmamıza benzer şekilde azaldığı görülmektedir [26,27]. Gouronti ve ark.…”
Section: Introductionunclassified